(untitled) (Tarbiyah Suska Conference Series, 2022)
This study aims to determine and analyze the intellectual character of junior high school students. Intellectual character is measured and analyzed through intellectual values ​​which are indicators of the formation of intellectual character in students, such as (1) curiosity; (2) open-mindedness; (3) intellectual courage; (4) intellectual thoroughness; and (5) attentiveness. This research is a descriptive research with survey method. The data collection technique uses a rating scale. Data were analyzed descriptively quantitatively. This research was conducted on 212 grade VIII students at SMP N 1 Sleman. The selection of samples selected by purposive sampling. The results showed that the intellectual character of students was in the moderate category, which was 37.26%. The intellectual character of students, such as curiosity, was achieved by 57.93%. The intellectual character of students, such as open mindedness, was achieved as much as 74.85%. The intellectual character of students, such as intellectual courage, was achieved as much as 63.74%. The intellectual character of students, such as intellectual thoroughness, was achieved as much as 64.96%. Students’ intellectual character, such as attentiveness, was achieved as much as 71.46%.